Macular profile of eyes developing macular holes in cases of central retinal vein occlusion treated with Bevacizumab - Khatri, Anadi; Karki, Pratap; Joshi, Sagun Narayan; Khatri, Bal Kumar; Kharel, Muna; Banstola, Amrit; Shrestha, Saurav Man (Journal of Kathmandu Medical College, 2020)
Background: Anti-vascular endothelial growth factors are commonly used for treatment for central retinal vein occlusion. There have been numerous reports regarding both the benefits and disadvantages of its use. Recently, a rather surprising complication- development of macular holes have started emerging. Objectives: The purpose of this study was to evaluate if the patient’s profile, baseline optical coherence tomography parameters, status of the vitreous and subsequent response pose a risk for macular hole formation in cases of central retinal vein occlusion central retinal vein occlusion following treatment with bevacizumab. Methodology: This prospective exploratory analytical study was conducted at a tertiary eye care center of Nepal and evaluated 97 eyes with central retinal vein occlusion undergoing treatment with bevacizumab. Results: Full Thickness Macular Hole developed in eight (8.24%) of the central retinal vein occlusion eyes treated with bevacizumab. Elderly age and eyes with cystoid edema at baseline were found to have greater risk of developing macular hole following treatment (OR: 8.97 , p<0.05). Twelve eyes (12.3%) of the eyes treated developed vitreoretinal interface anomalies and were the result of dramatic decrease in central macular thickness . All of them had cystoid macular edema at baseline. Five of them (42%) developed full thickness macular hole. Conclusion: Anti-vascular endothelial growth factor agents have been widely accepted as the first line of choice for treatment of macular edema secondary to central retinal vein occlusion. Cystoid macular edema, eyes of the elderly and those showing dramatic decrease in central macular thickness with the development of anomalous vitreoretinal interface are potential risk factors for full thickness macular hole.